Soviet Armed Forces in Lithuania in 1939–1941 - Miknevičius, Gintautas (Genocidas ir rezistencija, 2021)
During the first period of bringing the Soviet armed forces into the country, Soviet officers remained neutral in Lithuania for some time, however, they violated the Lithuanian border on the frontier, kidnapped our ordinary citizens and officials under the false pretext and tried to obtain information about the Lithuanian Armed Forces from them. After Germany had launched an attack on France, the situation changed and the behaviour of the Soviet military officers became more impudent; they used their deserters as a means of blackmail and pressure on Lithuania. Soviet military documents stored in the Lithuanian Special Archives show that it was on the third and the fourth of June, 1940 that the Soviet armed forces were started to be concentrated to occupy Lithuania. It becomes clear that the fate of the Lithuanian State was decided during the first days of June already. In the evening of 15 June, in the territory of Belarus, a new agreement signed on the deployment of the new Soviet military divisions established the occupation. The title of the reporting package of the Soviet documents Description of Combat Work of 3 Military Units and Divisions of the Armed Forces in the Baltics Campaign proves that this was a military operation of the Soviet Union – to occupy Lithuania and other Baltic countries. Utterances and statements of high-ranking Soviet officers claiming that Lithuania surrendered and accepted the ultimatum also confirm that. Instructions, prohibitions and orders issued by the Soviet military officers to the military of Lithuania, self-will and abuse of Soviet military disregarding all laws of Lithuania clearly show that the Soviet armed forces behaved as an occupying army.
Keywords: soviet occupation; soviet armed forces; soviet crimes; repressions